2008
DOI: 10.1002/glia.20639
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes produce interferon‐alpha and CXCL10, but not IL‐6 or CXCL8, in aicardi‐Goutières syndrome

Abstract: Aicardi-Goutières syndrome (AGS) presents as a severe autosomal recessively inherited neurological brain disease. Clinical and neurological manifestations closely resemble those of congenital viral infection and are generally attributed to a perturbation of innate immunity including a long lasting lymphocytosis and production of interferon-alpha (IFNalpha) in the central nervous system. To clarify the innate immune response evoked in these diseases, we used a 30-mer multiplexed luminex system to measure multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
81
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 60 publications
9
81
3
Order By: Relevance
“…Even though IFN-a is considered to be a key biomarker for AGS, the chemokine CXCL10 has also been persistently demonstrated to have an elevated expression in AGS patients (12,13). Consistent with this, our study shows that silencing AGS genes results in an increased expression and release of CXCL10 mainly in astrocytes.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Even though IFN-a is considered to be a key biomarker for AGS, the chemokine CXCL10 has also been persistently demonstrated to have an elevated expression in AGS patients (12,13). Consistent with this, our study shows that silencing AGS genes results in an increased expression and release of CXCL10 mainly in astrocytes.…”
Section: Discussionsupporting
confidence: 87%
“…IFN-a is a wellknown potent antiangiogenic factor and is therefore used as coadjuvant therapy in different types of cancer (44). Second, the levels of IFN-a remain sustainably high for years in both serum and CSF (12,45). Third, a general downregulation of angiogenesis-related genes has been described for AGS patients carrying different genotypes (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional knowledge of the zebrafish specific chemokine cxc46 is relatively poor. However, other CXC chemokine family members are upregulated in response to viral infection in zebrafish larvae (18), and increased expression of chemokines has been reported in AGS (42,43). Increased expression of genes encoding the transcription factors irf1b, irf7, stat1b, and cebpb, as observed in our morphants, has also been recorded following exposure to two viruses in zebrafish infection models (18), and significant upregulation of the human orthologs, STAT1 and IRF7 is seen in AGS (7).…”
Section: Discussionsupporting
confidence: 52%
“…Upregulation of both transcripts was confirmed by RT–qPCR, and ELISA of culture supernatants from all six Rnaseh2b −/− lines demonstrated significantly increased CCL5 and CXCL10 secretion (Fig 3D and E, and Appendix Fig S2B). Notably, these cytokines have previously been implicated in AGS neuroinflammation in humans (van Heteren et al , 2008; Takanohashi et al , 2013; Cuadrado et al , 2015). We therefore concluded that impaired RNase H2 activity in vitro and in vivo results in a similar inflammatory response to that observed in patients with AGS, and like for Trex1 deficiency (Gall et al , 2012) is present in non‐immune cells.…”
Section: Resultsmentioning
confidence: 96%